2018
DOI: 10.1080/09291016.2018.1447353
|View full text |Cite|
|
Sign up to set email alerts
|

TheDrosophila apterous56fmutation impairs circadian locomotor activity

Abstract: We investigated effects of apterous mutation ap56f on circadian locomotor activity, eclosion rhythms, and transcript levels of period and timeless in Drosophila. We investigated circadian locomotor activity and eclosion rhythms in ap56fand wild-type flies, their F1 and F2 offspring, and wingless vestigial mutants and show that ap56f disrupts circadian locomotor rhythms in a genetically recessive manner, that is not caused by the absence of wings. The apblt strain also showed impaired circadian activity rhythms… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 21 publications
1
4
0
Order By: Relevance
“…Both seasonal influence and its interactions with farming systems were also noticed with higher scores in summer season. Similar relation of panting score with heat stress was proposed by several author [ 6 , 19 21 ]. Panting score is a measure of respiratory rate and body temperature.…”
Section: Discussionsupporting
confidence: 78%
See 3 more Smart Citations
“…Both seasonal influence and its interactions with farming systems were also noticed with higher scores in summer season. Similar relation of panting score with heat stress was proposed by several author [ 6 , 19 21 ]. Panting score is a measure of respiratory rate and body temperature.…”
Section: Discussionsupporting
confidence: 78%
“…The lipid peroxidation increases the fragility of RBC membrane, consequently increasing the EOF [ 24 , 25 ]. During heat stress periods, the high panting score led- respiratory alkalosis will increase the fragility of RBC, thereby increasing the EOF [ 6 ]. Few authors reported the increased EOF even in extreme cold climatic seasons [ 26 ] or transport stress [ 25 ], revealing that the EOF could be increased in stress, irrespective of the type.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In this line, evening-type persons, who are the mainly social jet-lag sufferers, must perform different functions (sleep and wake-up, eat, work, study, child care, etc.) in a schedule that is unadjusted to their biological clock, which might be understood as upstream swim, that might result in higher fatigue as it has been observed in previous works [83][84][85]. In this line, longitudinal studies are needed to analyze if this worse emotion regulation strategies together with the maladaptive metacognitive style and the lower assertiveness observed in those participants closer to the eveningness pole might be the result of this higher fatigue.…”
Section: Plos Onementioning
confidence: 83%